2017
DOI: 10.1002/oby.21765
|View full text |Cite
|
Sign up to set email alerts
|

miRNAs in human subcutaneous adipose tissue: Effects of weight loss induced by hypocaloric diet and exercise

Abstract: Weight loss influenced several miRNAs, some of which were negatively correlated with predicted targets. These dysregulated miRNAs may affect adipocytokine signaling and forkhead box protein O signaling.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
31
0
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(34 citation statements)
references
References 38 publications
(46 reference statements)
0
31
0
3
Order By: Relevance
“…Indeed, previously published work demonstrates that in a cohort of 66 men and women, ranging from lean to obese, miR-29a in visceral and subcutaneous WAT is negatively correlated with BMI 20 . A second human study found an increase in miR-29a in subcutaneous WAT from 19 obese individuals following diet and exercise-induced weight loss 29 .…”
Section: Figmentioning
confidence: 99%
“…Indeed, previously published work demonstrates that in a cohort of 66 men and women, ranging from lean to obese, miR-29a in visceral and subcutaneous WAT is negatively correlated with BMI 20 . A second human study found an increase in miR-29a in subcutaneous WAT from 19 obese individuals following diet and exercise-induced weight loss 29 .…”
Section: Figmentioning
confidence: 99%
“…Recent years, the number of microRNA profiling studies has increased rapidly. MicroRNAs profiles in several different tissues were investigated after CR, EX or HF, including adipose tissue, skeletal muscle, heart, especially circulating microRNAs [13][14][15][16]. There are only few microRNAs profiling studies in liver under these lifestyle modification conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, these three miRNAs were shown to be expressed in AT. Let‐7f has been reported to be highly expressed in ovine AT , while miR‐296 was highly expressed in both ovine visceral AT (VAT) and subcutaneous AT (SAT) , and miR‐20b‐5p was significantly elevated in human SAT , suggesting the potential regulatory mechanisms that these miRNAs could play in AT regulation. Accordingly, in this study, we analyzed the expression levels of miR‐20b, miR‐296, and Let‐7f in human VAT and SAT in relation to obesity and T2D and dissected their gene interaction network using bioinformatic prediction analysis, with a focus on TGs that are related to the pathogenesis of both obesity and T2D.…”
Section: Introductionmentioning
confidence: 99%